Physical Activity and Risk Factors Screening for Ischaemic Heart Disease in South African Individuals Living with HIV - Ronel, Roos; Hellen, Myezwa; Helena, van Aswegen; Eustatius, Musenge (Journal of Clinical Research In HIV AIDS And Prevention, 2016)
People living with HIV (PLWH) are at risk of developing chronic lifestyle diseases such as ischaemic heart disease (IHD). Physical inactivity is a modifiable risk factor for IHD. The level of ambulation physical activity in individuals living with HIV in a South African context is unknown. The aim of this study was to assess the physical activity levels and other risk factors for IHD in PLWH on antiretroviral therapy (ARV). An observational study was conducted from October 2010 to June 2012 at an outpatient clinic in Johannesburg, South Africa. Two hundred and five individuals who were on ARV for 6-12 months were screened. Physical activity was measured with the Yamax SW200 pedometer over a seven day period. Physical activity of the sample was reduced at 7673.2 (±4017.7) steps/ day with women walking less than men 6993.3 (±3462.6) and 10076.3 (±4885.6)respectively. Body mass index was increased to 25.6 (±5.4) kg/m2 with women noted to be overweight [26.6 (±5.5) kg/m2]. Independent predictors of being overweight were systolic blood pressure, waist and hip circumference, CD4 count and daily fruit and vegetable intake. Smoking was less common in the study population with 16.1% of the sample being current smokers and 25.9% former smokers. Individuals’ mean perceived stress levels were 19.9 (±7.8) on the Cohen’s Perceived Stress Scale. The ambulation physical activity level of individuals living with HIV requires modification to assist with reducing risk factors of IHD.
Keywords: Physical activity level; HIV; ischemic heart disease